A brave new world: the gastrointestinal lab during and after a pandemic. Issue 1 (January 2022) - Subramaniam, Sharmila; Al-Kandari, Asma; Bhandari, Pradeep
Abstract : Purpose of review: The COVID-19 global pandemic resulted in a radical change in the provision and delivery of endoscopy services worldwide. As we emerge from this pandemic, various strategies were advocated to resume endoscopy whilst prioritizing the safety and wellbeing of patients and staff. Recent findings: This review summarizes the main changes including infection control and prevention measures in endoscopy and explores the overarching impact of the pandemic on the gastrointestinal lab. Various solutions are outlined to enable the well tolerated resumption of endoscopy services including retention of certain infection control measures, use of personal protective equipment, testing and vaccination. Strategies to deal with the mounting backlog of cases are also discussed. Summary: The COVID-19 pandemic wreaked havoc on healthcare systems worldwide and affected the provision and delivery of gastrointestinal diagnostic services, such as endoscopy necessitating a new way of working and an emphasis on infection control and better use of technology that are likely to be here to stay in the post pandemic era.